2016
DOI: 10.1139/cjas-2015-0148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of live yeast on immune responses and intestinal morphological structure in lipopolysaccharide (LPS)-challenged broilers

Abstract: The effects of live yeast (LY) on immune responses and intestinal morphological structure in lipopolysaccharide (LPS) challenged broilers were investigated. A total of 480 one-day-old male broilers were divided into six groups following a 3 × 2 factorial arrangement (eight replicates) with three dietary LY dosages (0%, 0.05%, or 0.50%) and two immune treatments (injection of saline or LPS) given at an interval of 48 h between 21 and 27 d of age. Blood was sampled on days 21 and 27, while intestine were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Dietary inclusion of yeast-derived products could increase serum IgG in broilers (Ding et al 2019) which justified our current finding for serum immunity. Live yeast cell wall could produce some trophic substances and has a role as an immune cofactor (Wang et al 2017). Higher IgG in colostrum and milk was also recorded in sows fed with live yeast S. cerevisiae during the later stage of gestation (Zanello et al 2013).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Dietary inclusion of yeast-derived products could increase serum IgG in broilers (Ding et al 2019) which justified our current finding for serum immunity. Live yeast cell wall could produce some trophic substances and has a role as an immune cofactor (Wang et al 2017). Higher IgG in colostrum and milk was also recorded in sows fed with live yeast S. cerevisiae during the later stage of gestation (Zanello et al 2013).…”
Section: Discussionmentioning
confidence: 90%
“…Improvement in the intestinal morphological structure, involving higher villus height, villus height to crypt depth ratio, and lower crypt depth, was useful for nutrient utilization, stress resistance, and gut barrier function in livestock animals (Viveros et al 2011;Wang et al 2017;Tufail et al 2019). This experiment ensured the higher villus height and the higher ratio of villus height, and crypt depth in jejunum and ileum with live yeast supplemented groups that were associated with the higher nutrient retention as well as higher average daily weight gain at the finisher period in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muthusamy et al [15] obtained positive modification of histomorphology of the intestinal mucosa of broilers with both live yeast and pellets of the yeast cell wall. Wang et al [16] confirmed the beneficial activity of the live yeast, recording an improved villus surface area and villus width in the ileum of lipopolysaccharide-challenged broilers.…”
Section: Introductionmentioning
confidence: 89%
“…Generally, the increased circulating activity of DAO is associated with injured intestinal integrity and barrier function. When the intestinal epithelium is damaged, DAO is released into blood vessels, resulting in elevation of blood DAO (Wang et al, 2016). In the current study, compared to GNY, GRY increased DAO activity in serum, indicating that the intestinal barrier function was impaired.…”
Section: The Differences Of Permeability Parameters In Serum Between mentioning
confidence: 49%